The need to succeed – learning experiences resulting from the implementation of value-based healthcare. Issue 1 (25th October 2017) - Nilsson, Kerstin; Bååthe, Fredrik; Erichsen Andersson, Annette; Sandoff, Mette
Abstract : Purpose: The aim of this study has been to explore learning experiences from the two first years of the implementation of value-based healthcare (VBHC) at a large Swedish University Hospital. Design/methodology/approach: An explorative design was used in this study. Individual open-ended interviews were carried out with 19 members from four teams implementing VBHC. Qualitative analysis was used to analyse the verbatim transcripts of the interviews. Findings: Three main themes pinpointing learning experiences emerged through the analysis: resource allocation to support implementation, anchoring to create engagement and dedicated, development-oriented leadership with power of decision. Resource allocation included the need to set aside time and administrative resources and also the need to adjust essential IT-systems. The work of anchoring to create engagement involved both patients and staff and was found to be a never-ending task calling for deep commitment. The hospital top management's explicit decision to implement VBHC facilitated the implementation process, but the team leaders' lack of explicit management mandate was experienced as obstructing the process. The development process contributed not only to single-loop learning but also to double-loop learning. Originality/value: Learning experiences drawn from implementing VBHC have not been studied before, and thus the results of this study could be of importance to managers and administrators wanting to implement this concept in their respective organizations.